Application of X-ray computed tomography in soil and plant -a review - Ghosh, Tridiv; Maity, Pragati Pramanik; Rabbi, Sheikh M. F.; Das, T. K.; Bhattacharyya, Ranjan (Frontiers in Environmental Science, 2023)
X-ray computed tomography (X-ray CT) is a non-destructive method of soil analysis which can provide three-dimensional (3D) view, quantitative information of the internal organization of the soil. In this paper, we discuss the potential application of X-ray CT in characterization of soil properties like porosity and pore size distribution (PSD), root architecture, soil phase classification, water and solute transport in soil, and highlight the research during last 10-15 years. Here, we review the recent development of X-ray CT in soil science, use of artificial intelligence and machine learning in image analysis, point out the major challenges associated with its use, discuss few improvements to overcome these difficulties and elaborate the possible future technological developments for non-invasive/destructive soil characterization by integrating X-ray CT with recently available complementary techniques.